Techno-Economic and Exergetic Performance of Waste Heat Recovery Systems in Automotive Manufacturing Plants: A Comprehensive Review and Case Integration - Tri Murniati (CV. Indie Press Edutaste, 2026)
The rapid evolution of automotive manufacturing toward industrial decarbonization has underscored the critical importance of effective thermal energy management. Despite numerous studies on energy efficiency, there remains a persistent knowledge gap regarding the integration of thermodynamic performance and techno-economic viability in complex manufacturing environments. This study aims to provide a comprehensive synthesis of waste heat recovery (WHR) system applications within automotive production facilities. By utilizing a systematic review methodology, 70 core peer-reviewed publications were analyzed to map current technological landscapes and efficiency trends. The findings reveal that system performance is strongly dictated by source temperature characteristics, with heat exchangers and expansion valves identified as the primary zones of exergy destruction. Furthermore, techno-economic evaluations indicate that WHR installations achieve positive net present values within an average operational period of four to six years. This review contributes to the field by bridging first-law energy analysis with second-law exergetic perspectives to establish a unified framework for industrial energy assessment. Ultimately, the results suggest that manufacturing plants should prioritize integrated hybrid energy systems to maximize thermal efficiency. Future research is strongly recommended to incorporate artificial intelligence-driven predictive control models to enhance energy recovery in dynamic operating conditions.